Livestock in the Household Economy: Cross‐Country Evidence from Microeconomic Data. (January 2015) - Pica‐Ciamarra, Ugo; Tasciotti, Luca; Otte, Joachim; Zezza, Alberto
<x xml:space="preserve">Abstract</x> The development of the livestock sector can contribute to economic growth and poverty reduction, but there is inadequate understanding of livestock‐livelihoods linkages. This article draws on household‐level data from 12 developing countries to investigate the livestock‐asset position of rural households and its contribution to their income. The majority keep livestock; the less well‐off are more likely to keep livestock than the better‐off, but the very poor often lack the resources to invest in small animals. The key policy conclusion is that, contrary to common belief, there are no universal messages about livestock: policy needs to be tailored to farming systems, species, uses of livestock and different wealth groups.